Lateral load carrying capacity of piles in Bangkok subsoil - Prawat Teerasawat; Surachat Sumphdntharak; Balasubramaniam, A.S.; Ohta, Hideki; The Australian Government (Bangkok : Asian Institute of Technology, 1981)
Recent experimental investigations a nd advances in analytical techniques have added greatly to the general understanding of the problem of laterally loaded pile. However, a lack of field performance and field cases to cofired the validity of these techniques still exists, especially of long prestressed concrete piles in f:! a11 gk0Jt subsoil condition. Lateral pile load tests were carried out on five long prestressed concrete piles of rectangular section having the sizes ranging from 0.35x0.35 m. to 0.45x0.45 m. and approximately 24 .0 m. long . The test results show that there is time-d pendent effect on lateral deflection of piles, resulting from the present of very soft Bangkok clay at Bang Pakong Thermal Plant Project. Th e increasing of pile stiffness reduces the lateral deflection. Soil properties near the pile top significantly influence the pile movement, especially when Small movement is allowed . As a result , the sand fill is found to significantly reduce the lateral deflection. The repeated loading increases the lateral deflection and most oi the influence of repeated loading occurs in the first several repetition. several analyses have been done to compare will the situ test results. It show that the approach presented by DAVISSON & GILL ( 1963) using soil parameters from unconsolidated undrained triaxial tests for obtaining soft clay modulus, and plate loading tests for sand fill, was suitable to predict lateral deflection of pile in two layered soil consisting of the approximate 2.0 m. of sand fill overlying the 14.0 m. deposit of highly sensitive very soft marine clay having the natural water content over 100%.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 1981
Keywords: Soil mechanics -- Thailand -- Bangkok -- Research; Prestressed concrete construction -- Testing; Piling (Civil engineering) -- Testing